Óleos essenciais no controle de Corynespora cassiicola da soja - Mariotto, Axel Bruno (2023)
The increase in agricultural production in recent years highlights some problems that were previously nothing more than minor obstacles, but with the expansion of crops in many regions of Brazil, there has been a concomitant increase in phytosanitary problems, being one of the greatest challenges for soybean farmers. Soybean has excellent chemical application programs for the main diseases, but secondary diseases currently stand out, such as Target Spot, caused by Corynespora cassiicola, which is pathogenic to several hosts and with potential resistance to several fungicides. The use of essential oils and their major chemical constituents in phytosanitary management comes as an alternative method to chemical control, aiming at lower risk to the environment and the selection of resistant pathogens. The objective of the present work was to evaluate the action of essential oils from eight species of aromatic plants in nine doses, in the control of mycelial growth of C. cassicola and to verify the inhibition of ergosterol synthesis in the plasmatic membrane of the fungus. The work was carried out in two experiments, the first was the in vitro antifungal activity of essential oils. The second was the effect of essential oils on inhibiting ergosterol synthesis. The two experiments were carried out at the Federal University of Santa Maria, Frederico Westphalen campus in the year 2022. The in vitro experiment had a completely randomized experimental design in a bifactorial 8 x 9 scheme, with eight essential oils OE1, OE2, EO3, EO4, EO5, EO6, EO7 and EO8) and nine doses (0.0; 0.3; 0.6; 0.9; 1.2; 1.5; 1.8; 2.1 and 2.4 µL mL -1 ), and using fluxapyroxad + pyraclostrobin-based fungicide (1.5 µL mL-1 ) for comparison purposes. Fungal growth assessments were performed over a period of 10 days. After this period, it was verified in the in vitro experiment that the essential oils OE1, OE2, OE3, OE4 and OE8 showed the best results demonstrating total inhibition of the pathogen, as well as the fungicide. For the ergosterol inhibition experiment, a dose of 1.5 µL mL-1 was evaluated, chosen based on the results obtained from the in vitro assay, the treatments were incubated in petri dishes similar to the previous experiment and after six days the It was found that the essential oils OE1, OE2, OE3, OE4, OE5 and OE8 showed the best results with total inhibition of the isolated ergosterol synthesis. The essential oils tested in the present work demonstrated satisfactory effects in the control of C. cassiicola and can be a viable alternative for its control.